Eculizumab for Hyperhemolysis in Sickle Cell Disease: Key Insights From a Challenging Case - Sruthi Vellanki; Anup Kumar Trikannad Ashwini Kumar; Nishanth Thalambedu; Cesar Gentille; Ankur Varma (Annals of Internal Medicine: Clinical Cases)
Hyperhemolysis (HS) is a rare but potentially fatal complication after blood transfusion in patients with sickle cell disease. This is indicated by a decrease in hemoglobin levels following the transfusion compared with pretransfusion levels. Management is complicated by difficulty arriving at a diagnosis and limited therapeutic strategies. We present a case of delayed HS in a patient with sickle cell anemia. She was refractory to steroids and intravenous immunoglobulin therapy and was treated with eculizumab and rituximab. This case underscores the potential of eculizumab in managing HS, offering new avenues for therapeutic intervention in this complex clinical scenario.